Risk Factors for Progression to Referable Diabetic Eye Disease in People With Diabetes Mellitus in Auckland, New Zealand: A 12-Year Retrospective Cohort Analysis. Issue 6 (November 2021) - Hill, Sophie; Mullins, Peter; Murphy, Rinki; Schmiedel, Ole; Vaghefi, Ehsan; Ramke, Jacqueline; Squirrell, David
Abstract : Purpose: To evaluate the prevalence and risk factors for the development of any and referable diabetic eye disease in a multi-ethnic New Zealand population with diabetes mellitus attending a regional retinal screening service. Methods: Retrospective observational cohort study of people living with diabetes who attended the Auckland Regional Diabetic Retinal Screening Programme 2006–2018 inclusive (n = 41, 786). Results: Any retinopathy/maculopathy was present at first screening for 48.2% [95% confidence interval (CI): 45.8%–50.6%] / 37.8% (95% CI: 35.5%– 40.1%) of people with Type 1 and 25% (95% CI: 24.6%–25.4%) / 21.9% (95% CI: 21.5%–22.3%) with Type 2 diabetes. Referable retinopathy at baseline screening was 4.4% (95% CI: 3.6%–5.3%) and 1.6% (95% CI: 1.5%–1.7%) among people with Type 1 and Type 2 diabetes mellitus, respectively. After 4 years, cumulative incidence for referable retinopathy /referable maculopathy was 12/36 per 1000 people with Type 1 and 2.4/16 per 1000 people with Type 2 diabetes. Independent hazards for disease progression varied for the diabetes cohort types but baseline grade, duration of diabetes, and HbA1c were common to all. Conclusions: Referable diabetic eye disease at the first screening and after 4 years of follow-up is uncommon. Lengthening of the screening intervals for people with no or mild diabetic eye disease at first screening assessment could be considered. Abstract : Supplemental Digital Content is available in the text